Anaphylaxis associated with intravenous administration of alphaxalone in a dog. Issue 6 (28th May 2019) - Haworth, M; McEwen, M; Dixon, B; Purcell, SL
Abstract : Case report: We describe the clinical signs and management of a case of anaphylaxis in a dog after intravenous administration of alphaxalone (Alfaxan®, Jurox, NSW, Aust), which has not been previously published. A female spayed cattle dog undergoing routine imaging for forelimb lameness was induced with Alfaxan after receiving sedation with acepromazine and methadone 70 min prior. Immediately after intravenous administration of Alfaxan, the dog exhibited vomiting and diarrhoea associated with acute hypotension. Gallbladder wall oedema was visualised consistent with anaphylaxis. The dog responded to rapid volume expansion. Adrenaline was not required. The dog made a full recovery within 6 h of the reaction and was re‐anaesthetised 3 days later without incident, using propofol as the induction agent. Conclusion: To our knowledge, this is the first published case of anaphylaxis associated with intravenous Alfaxan in the dog. The APVMA reporting of reactions in small animals from 2003 to 2013 of Alfaxan is consistent with this case report's finding involving the respiratory, circulatory and gastrointestinal systems.